Assessing community participation in the upgrade of informal settlements : a case study of the formalisation of the Democratic Resettlement Community, Swakopmund, Namibia - Ndalifilwa, Rosalia Mwafikange (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPA)--Stellenbosch University, 2019.